2002
DOI: 10.1046/j.1365-2648.2002.02174.x
|View full text |Cite
|
Sign up to set email alerts
|

Deliberate self‐harm in adolescence: a systematic review of psychological and psychosocial factors

Abstract: It is discussed whether associated factors are causative of DSH or the accompanying symptoms in DSH. It is suggested that positive psychosocial factors may have a part to play in providing protection against DSH behaviour. Therapeutic responses to DSH are suggested as preventative measures against repeat episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
71
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 17 publications
8
71
0
1
Order By: Relevance
“…Studies have also found that self-harmers are more likely to come from families characterized by divorce, neglect, and parental deprivation. Webb (2002) conducted a systematic review of the literature on the psychosocial factors 1 in DSH among adolescents that employed strict inclusion criteria (studies were excluded based on lack of original data, poor reporting or discrimination of details, or nonrelevant outcome measures). Most studies included both suicidal and nonsuicidal individuals, and none distinguished clearly between the two categories.…”
Section: Need and Conflictmentioning
confidence: 99%
“…Studies have also found that self-harmers are more likely to come from families characterized by divorce, neglect, and parental deprivation. Webb (2002) conducted a systematic review of the literature on the psychosocial factors 1 in DSH among adolescents that employed strict inclusion criteria (studies were excluded based on lack of original data, poor reporting or discrimination of details, or nonrelevant outcome measures). Most studies included both suicidal and nonsuicidal individuals, and none distinguished clearly between the two categories.…”
Section: Need and Conflictmentioning
confidence: 99%
“…Ailesel faktörlerin, başka dışsal faktörlerle birlikte ergenlerin sorunlarını çözme-de yetersizliğe neden olduğu ve KKZ davranışı için riskli psikolojik süreçlere yol açtığı öne sürülmektedir. Ayrıca uygun olmayan ailesel ve dışsal süreçlerin ergenlerin özsaygı ve kimlik oluşumuna olumsuz etki yaptığı, bunun kendine zarar verme ile ilişkisi saptanmış olan depresyon ve umutsuzluğa yol açtığı belirtilmiştir (Webb 2002).…”
Section: Ailesel Etkenlerunclassified
“…Non-suicidal self-injury (NSSI), or the act of purposefully harming one's physical self without suicidal intent, is an increasingly prevalent phenomenon that occurs in 13% to 20% of 2 adolescents (e.g., Lloyd-Richardson, Perrine, Dierker, & Kelley, 2007;Ross & Heath, 2002). This maladaptive behavior is often indicative of deeper internal or social problems and can act as a gateway to other negative risk behaviors, including drug use, smoking, bulimic behavior, aggression, sexual behavior, and, in some cases, suicide (Brown, Houck, Hadley, & Lescano, 2005;Guertin, Lloyd-Richardson, Spirito, Donaldson, & Boergers, 2001;Laye-Gindhu & Schonert-Reichl, 2005;Webb, 2002). Research over the past few decades has ventured to describe and deconstruct this dangerous behavior (Favazza, 1989(Favazza, , 1998Klonsky, 2007;Nock, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Girls are reported to engage in more impulsive self-injury, such as self-laceration, self-poisoning, and self-biting than boys (Madge, et al, 2008;Webb, 2002;White Kress, 2003). Girls are also more likely to report feeling the need to hurt oneself and report feeling unhappy or depressed as primary reasons for engaging in NSSI (e.g., Laye-Gindhu & Schonert-Reichl, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation